2013
DOI: 10.1590/s0100-29452013000200037
|View full text |Cite
|
Sign up to set email alerts
|

Curva de crescimento e padrão respiratório de frutos de genótipos de pessegueiro em região de clima subtropical

Abstract: RESUMO- GROWTH CURVE AND RESPIRATORY PATTERN OF GENOTYPES OF PEACH FRUIT IN SUBTROPICAL REGIONABSTRACT -The study aimed to determine the length of the cycle and characterize phases of the growth curve and the breathing pattern of peach genotypes grown in subtropical climate region. The experiment was conducted at the experimental orchard at the Universidade Federal de Viçosa (UFV) in Araponga-MG. It was selected ten genotypes from the breeding program at UFV where 50 fruits were collected biweekly from anthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
(5 reference statements)
3
7
0
1
Order By: Relevance
“…In 2014, the fruit growth behavior was as expected for peach fruits, according to Silva et al (2013). In this year, non-thinned plants showed lower fruit growth than those that had been thinned or headed, especially in the last assessment, which corresponds to stage III of growth.…”
Section: Resultssupporting
confidence: 57%
“…In 2014, the fruit growth behavior was as expected for peach fruits, according to Silva et al (2013). In this year, non-thinned plants showed lower fruit growth than those that had been thinned or headed, especially in the last assessment, which corresponds to stage III of growth.…”
Section: Resultssupporting
confidence: 57%
“…There are few studies on the growth curve of peach fruits in different regions of Brazil in the literature [14][15][16]. Researchers in other countries observed that difference in fruit size between genotypes has a strong genetic influence and is broadly explained by differences in the total number of cells in the mesocarp [3,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…A basic color tone was found, as shown in Figure 4, where it is expected to observe the climacteric respiratory peak at the end of maturation (Silva et al, 2013). The predominant base color at this stage is yellow associated with carotenoid content, meteorological conditions, variety, growth conditions, such as those found by Cremasco et al, (2016), and color intensities of peach in order of importance were: 8/8 5 Y, Y 8.10 2.5, 5 and 8/6, and 8/8 2.5 Y, depending on the maturation degree and variety (MORAIS et al, 2017, CREMASCO et al, 2016.…”
Section: Resultsmentioning
confidence: 91%